The Vargas Government (1930-1945) and the dynamics of import substitution in Brazil: the role of the State in production and territorial development (Research, Society and Development, 2020)
The 1930s in Brazil preserves one of the most important periods in the recent history of the country. From of “30s Revolution”, Brazil experiences significant changes both in the economic axis and in the perspective of international insertion, two concomitant processes, but of different origins that found a common denominator during the Vargas government. This paper starts from the perspective that the State had a sine qua non participation in the development process between 1930 and 1945, using the international context to strengthen industrializing policies and managing part of the production chain. This observation is important since, at appropriate times, the historical role of the State has been neglected. The dynamics of import substitution can be considered an appropriate development model for the time that guaranteed the bases of the Brazilian real entry in the capitalism industry. This paper was developed from secondary data with the method of qualitative research and bibliographic review.